Governance dan Penegakan Hak Pekerja atas Upah Lembur: Studi Kasus PT SAI Apparel Industries - Eka Fitriana; Lydyana Trisnaeni Martin; Nur Aulia Lathifah; Roselia Ariyanti; Kuswan Hadji (Universitas 17 Agustus 1945 Semarang, 2025)
This research analyzes the legal provisions regarding the obligation to pay overtime wages and legal options for workers if the company fails to provide overtime compensation. Overtime wages are the right of workers regulated in Law No. 13 of 2003 concerning Manpower which has been amended by Law No. 6 of 2023 and Government Regulation No. 35 of 2021. This study uses a case analysis of PT X in Semarang, which was accused of not paying overtime wages in full to its employees. The findings show that despite clear legal regulations, implementation faces various obstacles, such as inadequate supervision and lack of legal awareness. Employees whose rights are not met can pursue out-of-court (e.g. bipartite negotiation, mediation, conciliation, arbitration) and court channels through the labor court. Non-compliance with regulations on overtime pay not only impacts the economic situation of employees, but also causes imbalances in labor relations. This research recommends strengthening the labor inspection system, increasing transparency in the handling of working hours, increasing legal awareness among employees, and developing a more accurate time recording system to ensure the fulfillment of employee rights according to the applicable regulations.